Selection of key criteria for assessment tools for patients with rheumatoid arthritis - Anzhela Nogas; Igor Grygus (Kazimierz Wielki University, 2018)
The article discusses the main criteria for assessment tools for patients with rheumatoid arthritis, analyses the methods and questionnaires most commonly used in medical and rehabilitation practice, in particular, taking into account the International Functioning Qualification and the recommendations of the Ukrainian Association of Rheumatologists on the treatment of the disease. The purpose of the paper is to analyse and identify the main criteria for assessment tools for patients with rheumatoid arthritis. Materials and methods: analysis and synthesis of scientific data in the modern scientific and methodological literature and selection of the main assessment tools for patients with rheumatoid arthritis. Results. The examination of a patient with rheumatoid arthritis is based on determining the objective condition of all organs and systems, the condition of the affected joints, which is the key to establishing a diagnosis, planning and predicting a physical therapy programme. In the course of the study, we found that researchers use different criteria and methodological approaches to the rehabilitation examination of patients with rheumatoid arthritis. Usually, examination of a patient with rheumatoid arthritis is based on generally accepted methods, which include: finding out the patient's complaints; careful collection of anamnesis (history) of the disease; objective assessment of vital body systems; objective examination, palpation of affected joints; use of additional research methods. Conclusion. As a result of the analysis of scientific achievements in the modern scientific and methodological literature, we have identified the following main criteria for the assessment of patients with rheumatoid arthritis: determination of motor and functional disorders, VAS, Ketle index, MMT, goniometry, dynamometry, BCTQ, Sollerman hand function test, DASH, HADS, Stanford Health Assessment Questionnaire, and the EuroQol-5D-5L.